Prediction and prevention of preeclampsia by physicians in Brazil: An original study - Cunha Filho, Edson Vieira da; Rodrigues, Tamara Cristina Gomes Ferraz; Sandrim, Valeria Cristina; Veiga, Eduardo Carvalho de Arruda; Cavalli, Ricardo Carvalho (Frontiers in Global Women's Health, 2022)
Background Considering the worldwide importance of preeclampsia, especially in Brazil, the screening of pregnant women at greater risk of developing the disease and the application of preventive measures are essential. This study aimed to assess the medical performance in this context in Brazil. Methods A survey was developed to quantify the number of physicians who prescribe acetylsalicylic acid (ASA) and/or calcium for preeclampsia prevention. The survey was sent to all Brazilian obstetricians affiliated to the Brazilian Federation of OBGYN by email and WhatsApp. The survey remained opened for 6 months and included questions about the use of ASA and calcium, as well as about the use of a complementary test to predict preeclampsia. Results The sample consisted of 360 responding physicians and 100% coverage of responses from physicians from the five different regions of Brazil was obtained. The vast majority of respondents (94.72%) prescribe ASA to prevent preeclampsia, with 80.3% prescribing a dose of 100 mg/day. Calcium is prescribed by 83.9% of the respondents. The majority of the interviewed sample (58.6%) requests uterine artery Doppler imaging to predict preeclampsia and 31.7% do not request any additional test. When the analysis was performed by region, only the northern region differed from the other Brazilian regions regarding the use of ASA and calcium for preeclampsia prevention. While more than 90% of physicians in the other regions prescribe ASA, 40% in the northern region do not use it (p < 0.0001). Regarding calcium, 30% of physicians in northern Brazil do not use the drug for preeclampsia prevention, a percentage that also differs from the other regions where the medication is prescribed by 80 to 90% of physicians (p = 0.021). Conclusions The vast majority of Brazilian physicians prescribe low-dose aspirin and calcium carbonate to prevent preeclampsia in high-risk pregnant women. In addition to the identification of clinical risk factors, most doctors use Doppler of the uterine arteries as a predictive method. In the northern region of Brazil, physicians use aspirin and calcium less frequently for preventing preeclampsia compared to the rest of the country.